Proteomics analysis reveals IGFBP2 as a candidate diagnostic biomarker for heart failure. (March 2015) - Berry, Matthieu; Galinier, Michel; Delmas, Clement; Fournier, Pauline; Desmoulin, Franck; Turkieh, Annie; Mischak, Harald; Mullen, William; Barutaut, Manon; Eurlings, Luc W.; Van Wijk, Sandra; Brunner-La Rocca, Hans-Peter; et al.
Abstract: Background: Diagnostic biomarkers for heart failure (HF) such as the natriuretic peptides (NPs) are widely used but have limitations. Innovative biomarkers could provide improved diagnostic performance. Methods: We launched a prospective case–control proteomic study and investigated for polypeptides specific to HF through a capillary electrophoresis-mass spectrometry (CE-MS) proteomic analysis. The putative biomarker was identified by Orbitrap liquid chromatography-MS, validated by western blot, then by ELISA using plasmas from multicentric international cohorts. A rat model of HF was tested for biomarker expression levels. Results: We identified insulin like growth factor binding protein 2 (IGFBP2) as a new diagnostic biomarker for HF with a high sensitivity and specificity (AUC = 0.93; 95% CI, 0.89-0.96; p < 0.0001) in the local cohort and IGFBP2 levels provided an AUC of 0.943 (95% CI, 0.860-1.026) which gave a 87 % sensitivity in AHF and 90 % specificity at the cut off value previously determined in the discovery cohort, i.e. 556 ng/ml. ROC curve analysis of IGFBP2 and NTproBNP showed an AUC of 0.784 (95% CI, 0.744-0.820) for IGFBP2 and a significantly higher AUC of 0.927 (95% CI, 0.900-0.949) for NT-proBNP, p < 0.0001 in a Dutch cohort. In this cohort, the optimal cut off value for IGFBP2 gave a sensibility of 71% (95% CI, 66–76) and a specificity of 75% (95% CI, 65–83). Conclusion: IGFBP2 is a new biomarker to diagnose HF which could be used to provide additional information to the NPs. Animals models will help in the evaluation of the putative IGFBP2 regulated mechanisms in HF.